2020
DOI: 10.36681/tused.2021.53
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Grade 11 Physical Science Teachers Perceptions of Practical Work in MankwengCircuit, South Africa

Abstract: Practical work is critical to understanding science concepts. A case study was carried out to understand teachers' perceptions regarding practical work in Mankweng Circuit, South Africa. Four Grade 11 Physical Science teachers from different high schools were purposively selected. Data were collected through interviews, classroom observations, and teachers' portfolios. Results show that teachers' had different perceptions, enactment and motives regarding practical work. Teachers used demonstrations, narratives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Practical work is also used to develop cooperation, teamwork, communication, collaboration, and social skills in learners through instructional strategies that enhance learner-learner interactions. Practical work in science can be conducted through a variety of hands-on activities, such as experiments, laboratory work, investigations, field work, and projects (Kibirige & Maponya, 2021). Akuma and Callaghan (2019a) indicated that practical work can be computer-based in addition to other hands-on activities.…”
Section: Introductionmentioning
confidence: 99%
“…Practical work is also used to develop cooperation, teamwork, communication, collaboration, and social skills in learners through instructional strategies that enhance learner-learner interactions. Practical work in science can be conducted through a variety of hands-on activities, such as experiments, laboratory work, investigations, field work, and projects (Kibirige & Maponya, 2021). Akuma and Callaghan (2019a) indicated that practical work can be computer-based in addition to other hands-on activities.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore learners may autonomously be engaged in teaching and learning activities through observation and the problems they have asked and responses provided. Moreover, practical work or hands-on learning in sciences is largely striving to produce learner who has ability and capability of hearing, manipulating and observing the expected outcomes (Kibirige & Maponya, 2021). Unfortunately, students in some secondary schools are not given the opportunities to manipulate the materials and participate actively in doing practical work to prevent them from damaging the limited equipment available.…”
Section: Introductionmentioning
confidence: 99%